The Plausibility of Pure Religion: Olivier Roy's Thesis about the Separation between Religion and Culture - Herck, Walter van (Toronto journal of theology, 2019)
Video Abstract The Plausibility of Pure Religion: Olivier Roy's Thesis bout the Separation between Religion and Culture Download Original Video (95.7 MB)Get the Flash Player to see this video.addFlashMovie('d223e143','/doi/video_low/10.3138/tjt.2019-0097/Van-Herck_VIDEO_ABSTRACT_S.flv') In this article, we examine the plausibility of the concept of "pure religion" as it is put forward by Olivier Roy in his book Holy Ignorance: When Religion and Culture Part Ways (2010). First, we describe Roy's thesis of the separation of religion and culture; second, we establish the role and meaning of the concept of "pure religion" in his theory; and third, we investigate whether and to what extent it is a plausible notion.